244 Prevalence and clinical predictors of inappropriate direct oral anticoagulant dosage in octagenarians with atrial fibrillation. (8th December 2021) - Carbone, Andreina; Santelli, Francesco; Bottino, Roberta; Attena, Emilio; Mazzone, Carmine; Parisi, Valentina; D'Andrea, Antonello; Golino, Paolo; Nigro, Gerardo; Russo, Vincenzo
Abstract: Aims: Older age is associated with inappropriate dose prescription of direct oral anticoagulants. The aim of our study was to describe the prevalence and the clinical predictors of inappropriate DOACs dosage among octogenarians in real-world setting. Methods: Data for this study were sourced from the multicentre prospectively maintained Atrial Fibrillation (AF) Research Database (NCT03760874). AF patients aged ≥80 who received DOACs treatment 253 patients were selected. Participants were categorized as appropriate dosage, overdosage, or underdosage. Underdosage and overdosage were respectively defined as administration of a lower or higher DOAC dose than recommended in the EHRA consensus. Results: A total of 178 patients (71%) received appropriate DOACs dose and 75 patients (29%) inappropriate DOACs dose; among them 19 patients (25.6%) were overdosed and 56 (74.4%) were underdosed. Subgroup analysis demonstrated that underdosage was independently associated with male gender [OR = 3.15 (95% IC 1.45–6.83); P < 0.01], coronary artery disease [OR = 3.6 (95% IC 1.41–9.1); P < 0.01] and body mass index [OR = 1.27 (1.14–1.41); P < 0.01]. Overdosage was independently associated with diabetes mellitus [OR = 18 (3.36–96); P < 0.01], with age [OR = 0.76 (95% IC; 0.61–0.96); P < 0.05], BMI [OR = 0.77 (0.11; 0.62–0.97); P < 0.05] and with previous bleedings [OR = 6.4 (0.7; 1.43–28) P < 0.05]. There wasn't significant difference in thromboembolic, major bleeding events and mortality among different subgroups. Underdosage group showed a significatively lower survival compared with appropriate dose group ( P < 0.001). Conclusion: In our analysis, nearly one-third of octogenarians with AF received an inappropriate dose of DOAC. Several clinical factors increased the risk of DOACs' overdosage (diabetes mellitus Type II) or underdosage (male gender, coronary artery disease and higher body mass index). Octogenarians with inappropriate DOACs underdosage showed less survival.